PERFORMANCE STATUS ANALYSIS OF HIGH PRESSURE RUKAVS IN HYDRAULIC SYSTEM (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the high – pressure rukav (HPR)s in hydraulic excavators used in mining enterprises with external environmental-climatic effects, resistance to steep particles and hydraulic shocks generated by blasting processes, and the ability to withstand internal pressure.